NON-MUSLIM STUDENT NEEDS FOR THE AIK CURRICULUM AT MUHAMMADIYAH UNIVERSITY NORTH SUMATRA - Nurzannah Nurzannah; Nurman Ginting (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to describe the needs of non-Muslim students for Al-Islam and Kemuhammadiyahan courses at UMSU. This research uses a survey method. The data collection instrument used a questionnaire and interviews. The sampling technique was purposive sampling, which consisted of 10 non-Muslim students. The data collected were analysed, then interpreted, then concluded. The results of the study indicate that the needs of Non-Muslim students for AIK courses are standard requirements. This means that because the AIK course is a subject that must be followed by students regardless of religious background, they make the AIK course a fulfilment of lecture standards only. Even so, they want religion and worship courses not to be taught in the form of Islamic doctrine, but in the form of Islamologi courses, or the like. Meanwhile, the Muamalah and Muhammadiyah courses taught so far are not a problem. They also suggested that learning methods and strategies should be adapted to the appropriate needs of students.Keywords: The Need, AIK Courses, Non-Muslim Students